The Role of the Qaṭal in Maskilic Hebrew Prose Fiction 1857-1881 - Kahn, Lily (Hebrew studies, 2009)
This paper constitutes the first thorough examination of the role of the qaṭal form in the Maskilic Hebrew prose fiction written between 1857 and 1881. Its main contentions are that the Maskilic Hebrew qaṭal can serve as a marker of past tense, present tense, and irrealis and that it can convey both perfective and imperfective aspect. Thus, while the maskilic qaṭal is found in some of the same contexts as its biblical and rabbinic counterparts, its overall role does not correspond precisely to that of either canonical stratum of the language; moreover, it exhibits a degree of influence from its authors' Yiddish vernacular and bears certain similarities to Israeli Hebrew. I shall use extracts from short stories and novels by prominent maskilic authors such as P. Smolenskin, A. Mapu, S. J. Abramowitz, I. M. Dick, and R. A. Braudes to illustrate these points. The maskilic qaṭal overlaps with both Biblical and post-Biblical Hebrew in the presentation of perfective past actions such as preterites, for example, Smolenskin's לפתע נפתחה הדלת and pluperfects, for example, Dick's ןאז החלה להתנחם על כל אשר עשתה However, it corresponds to biblical rather than post-biblical usage when used in the apodosis of irreal conditions, for example, Abramowitz's ולוּ היה לאל ידו, כי אז הוריד לה קערת שמים and with reference to present states, for example, Mapu's אהבתי מאר את הורי Conversely, it differs from both Biblical and Rabbinic Hebrew while mirroring Israeli Hebrew and Yiddish in its presentation of imperfective past actions such as the past continuous; this can be seen in Braudes's נשמע בבית משק קולאופני המר המרכבה אשר נסער בה.